Sobre dos especies de Marsypianthes (Lamiaceae, Ocimeae) del noreste argentino - Mallo, Andrea Cecilia (2004)
The neotropical genus Marsypianthes (Lamiaceae: Ocimeae) includes nearly 6 species distributed from Mexico to Bolivia, Brazil and northeastern Argentina. In the present study Marsypianthes hassleri is confirmed and M. chamaedrys is a new report for the Argentinian flora. Morphological and geographical data, types, synonymy, retypification of M. hassleri, identification key and iconography are provided.